The Corruption Eradication Commission's Strategy for Reducing Corruption Crime in Indonesia - Puji Handoyo; Mufidah Mufidah (JOURNAL of LEGAL RESEARCH, 2021)
The existence of the Law on Eradicating Corruption (PPTK Law) became a hope for the Indonesian nation in eradicating corruption, but eradicating corruption cases continues to be difficult. Corruption is a disease that has infected the Indonesian people for a long time. Corruption has infiltrated all levels of government, including state-owned enterprises. This study investigates the risks of corruption to the Republic of Indonesia and the Corruption Eradication Commission's (KPK) strategy for reducing corruption in Indonesia. This study employs qualitative methods in conjunction with a literature and law approach. This study's data came from legislation, court decisions, legal theory, books, and legal journals. According to the findings of this study, the dangers of corruption in Indonesia resulted in four things: inefficiency, uneven distribution, stimulants (incentives) in an unproductive direction, and political alienation, community cynicism, and political instability. Strategies to reduce corruption through preventive efforts, such as law enforcement officials supervising various sectors, particularly the public sector, and establishing the National Action Plan to Eradicate Corruption (RAN-PK). Through education and religion, the prevention of criminal acts of corruption from the standpoint of Islamic law.